Role of Diffusion-Weighted Magnetic Resonance Imaging in Assessment of Liver Injury After Radioembolization - Durmaz, Emine Şebnem; Alış, Deniz; Baş, Ahmet; Asa, Sertaç; Sager, Sait; Gülşen, Fatih (Cerrahpaşa Medical Journal, 2023)
Objective: We aimed to investigate the diagnostic value of diffusion-weighted imaging in assessing liver injury after radioembolization via comparing pre- and post-treatment apparent diffusion coefficient values of nontumoral liver parenchyma in patients who underwent radioembolization. Methods: We retrospectively examined the apparent diffusion coefficient values of the nontumoral liver parenchyma in 21 patients who underwent radioembolization. The observers placed the ellipsoid region of interest onto the nontumoral liver parenchyma using diffusion-weighted images, and then these regions of interest were transferred to apparent diffusion coefficient maps. The paired t-test was used to compare the change between pre- and post-treatment apparent diffusion coefficient values of the treated and the contralateral liver lobe. Results: The mean apparent diffusion coefficient value of the treated lobe was 1079.416 ± 194.57 mm2/s before and 963.10 ± 171.87 mm2/s after the treatment. A significant difference was observed between pre- and post-treatment mean apparent diffusion coefficient values of the treated lobe (P = .001). The mean apparent diffusion coefficient value of the contralateral lobe was 1114.24 ± 110.63 mm2/s before and 1116.20 ± 96.52 mm2/s after the treatment. No difference was observed between pre- and post-treatment mean apparent diffusion coefficient values of the contralateral lobe (P = .057). Conclusion: We observed reduced apparent diffusion coefficient values in the treated lobe of the liver, and our results suggest that reduced apparent diffusion coefficient values might reflect liver injury secondary to radioembolization. Cite this article as: Durmaz EŞ, Alış D, Baş A, Asa S, Sager S, Gülşen F. Role of diffusion-weighted magnetic resonance imaging in assessment of liver injury after radioembolization. Cerrahpaşa Med J. 2023;47(2):135-140.